Promoting Environmental Democracy: comments submitted by the SAHR towards the UN Human Rights Council in October 2023 | International Council on Archives - Section on Archives and Human Rights (SAHR) (International Council on Archives (ICA), 2023)
ICA SAHR commends the preparation of a comprehensive report by the Special Rapporteur on Human Rights and the Environment on ‘Promoting Environmental Democracy: procedural elements of the human right to a clean, health and sustainable environment’
Keywords: 2023-09 September; Environmental Democracy